2016
DOI: 10.1016/j.juro.2016.03.175
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparative Study of Color Doppler Ultrasound with Twinkling and Noncontrast Computerized Tomography for the Evaluation of Acute Renal Colic

Abstract: The initial use of color Doppler ultrasound in the emergency room has led to the diagnosis and characterization of ureteral stones in the majority of patients. Color Doppler ultrasound results were comparable to those of the concomitant use of noncontrast computerized tomography. Therefore, color Doppler ultrasound can replace noncontrast computerized tomography in the emergency room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 22 publications
1
29
0
2
Order By: Relevance
“…First, a randomized controlled trial by Smith-Bindman et al compared CT to ultrasound as initial imaging choice and found no increase in adverse outcomes in the ultrasound group and less overall radiation exposure [4]. Second, Abdel-Gawad et al demonstrated that the addition of the “twinkling effect” may increase the ability of ultrasound to detect kidney stones to nearly the same sensitivity as non-contrast CT scan [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a randomized controlled trial by Smith-Bindman et al compared CT to ultrasound as initial imaging choice and found no increase in adverse outcomes in the ultrasound group and less overall radiation exposure [4]. Second, Abdel-Gawad et al demonstrated that the addition of the “twinkling effect” may increase the ability of ultrasound to detect kidney stones to nearly the same sensitivity as non-contrast CT scan [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite such a high frequency of visits, controversy exists over the process of diagnosing obstructing kidney stones, as it has evolved over the past two decades [28]. Current evidence supports the use of both non-contrast CT and ultrasound [3,911]. The American College of Emergency Medicine’s “Choosing Wisely” recommendation states that clinicians should “avoid ordering CT of the abdomen and pelvis in young otherwise healthy emergency department (ED) patients (age <50) with known histories of kidney stones, or ureterolithiasis, presenting with symptoms consistent with uncomplicated renal colic,” but guidelines for the diagnosis of first-time kidney stones do not exist within the Emergency Medicine literature [12].…”
Section: Introductionmentioning
confidence: 99%
“…Die sonographische Darstellung des Harntrakts ist sicher, kann den Aufenthalt in der Notaufnahme signifikant verkürzen [5] und führt zudem zu keinem relevanten Zeitverlust bis zu einer eventuellen Intervention [6,7]. Der Farbdopplerultraschall eignet sich in der akuten Kolik für die initiale Diagnose eines Harnleitersteins und ist mit den Ergebnissen des Steinsuch-CT vergleichbar [8,9]. Der US führt zwar zu einer Überschätzung der Steingröße [10,11] aber über spezielle US-Einstellungen (S-Mode) und die Messung der Schallschattenbreite ist eine genauere, mit dem nativen CT vergleichbare Größenbestimmung möglich [12,13].…”
Section: Ultraschallunclassified
“…18 Abdel-Gawad and colleagues demonstrated in a prospective, radiologist blinded study of 815 patients that color Doppler ultrasound (CDU) was able to identify 97.1% of patients with ureteral stones, with an associated 97.2% sensitivity and 99% specificity. 19 A strength of this study was that multiple ultrasound machines were each able to reproduce the twinkling effect. These results may have been limited by an absence of evaluation of intra-and inter-observer variability, and these imaging studies require expertise in performing both graded compression of the ureter and interpreting this novel technique.…”
Section: Pediatric and Pregnant Patientsmentioning
confidence: 99%